Yarn bombing : the art of crochet and knit graffiti - Moore, Mandy, 1975- (Arsenal Pulp Press, 2009)
On city street corners, around telephone posts, through barbed wire fences, and over abandoned cars, a quiet revolution is brewing. "Knit graffiti" is an international guerrilla movement that started underground and is now embraced by crochet and knitting artists of all ages, nationalities, and genders. Its practitioners create works of art out of yarn, then "donate" them to public spaces as part of a covert plan for world yarn domination. This is the definitive guidebook to covert textile street art, featuring twenty kick-ass patterns that range from hanging shoes and knitted picture frames to balaclavas and gauntlets, and teaching readers how to create fuzzy adornments for lonely street furniture. Along the way, it provides tips on stealth, demonstrates how to orchestrate a large-scale project, and offers information to design your own yarn graffiti tags. Also includes interviews with members of the international community of textile artists and yarn bombers.--From publisher description.